UPAYA MENINGKATKAN HASIL BELAJAR GULING BELAKANG PADA SISWA KELAS XI IPA 3 MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DI SMAN 1 BANJARBARU - Aldi Rio komatsu, Jhoni; Purnama Indah, Eka; Sani, Abdullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to use the STAD cooperative learning model to determine whether students of class XI IPA 3 SMAN 1 Banjarbaru had improved their learning outcomes in the basic movement of backward rolls in floor gymnastics. The researcher collaborated with the Physical Education, Sports, and Health teacher to conduct Classroom Action Research (CAR). The planning, implementation, observation, and reflection stages of this study were divided into two cycles. Data from this study were obtained from tests, documentation, interviews, and observations. After that, the data went through three steps of analysis: data reduction, data presentation, and conclusion making. With an average score of 77.88, student learning outcomes in Cycle I showed a completion rate of 40%. However, some students still had difficulty practicing the basic movement method of backward rolls. However, the completion of learning outcomes significantly increased to 100% with an average score of 89.76 after the application of the STAD cooperative learning model in Cycle II. Therefore, this study leads to the conclusion that the STAD cooperative learning model can improve learning outcomes in the basic movement of backward rolls in floor gymnastics.